Combined local hypothermia and recanalization therapy for acute ischemic stroke: Estimation of brain and systemic temperature using an energetic numerical model. (August 2019) - Lutz, Yannick; Loewe, Axel; Meckel, Stephan; Dössel, Olaf; Cattaneo, Giorgio
Abstract: Local brain hypothermia is an attractive method for providing cerebral neuroprotection for ischemic stroke patients and at the same time reducing systemic side effects of cooling. In acute ischemic stroke patients with large vessel occlusion, combination with endovascular mechanical recanalization treatment could potentially allow for an alleviation of inflammatory and apoptotic pathways in the critical phase of reperfusion. The direct cooling of arterial blood by means of an intra-carotid heat exchange catheter compatible with recanalization systems is a novel promising approach. Focusing on the concept of "cold reperfusion", we developed an energetic model to calculate the rate of temperature decrease during intra-carotid cooling in case of physiological as well as decreased perfusion. Additionally, we discussed and considered the effect and biological significance of temperature decrease on resulting brain perfusion. Our model predicted a 2 °C brain temperature decrease in 8.3, 11.8 and 26.2 min at perfusion rates of 50, 30 and 10 ml 100 g ⋅ min, respectively. The systemic temperature decrease - caused by the venous blood return to the main circulation - was limited to 0.5 °C in 60 min. Our results underline the potential of catheter-assisted, intracarotid blood cooling to provide a fast and selective brain temperature decrease in the phase of vessel recanalization. This method can potentially allow for a tissue hypothermia during the restoration of the physiological flow and thus a "cold reperfusion" in the setting of mechanical recanalization. Highlights: Blood cooling with an intra-carotid heat exchange catheter is a novel approach for providing cerebral neuroprotection. An energetic model can predict the temperature decrease during cooling to evaluate the concept of a cold reperfusion. Brain temperature decreases of 2 °C in 8.7 min (physiological perfusion) or in 26.2 min (ischemic perfusion) are predicted. Measured in-vivo animal data show a similar temperature curve compared to the numerical simulation. The results show the potential of the new catheter to enable fast and selective brain cooling in the phase of recanalization.